Geology and Wine 12. New Zealand Terroir - Imre, Stephen; Mauk, Jeffrey (Geoscience Canada, 2009)
SUMMARY New Zealand produces premium quality wines and its wine industry is growing rapidly. The winegrowing regions have growing degree-days that range from 900 in cool Central Otago and Canterbury, to more than 1600 in the warmest region in the country, Auckland. Average growing season temperatures for the same regions range from approximately 14.3°C to 17.6°C. Most trophy-winning red wines are grown in areas with a climate cooler than where similar wines are grown to high standard internationally. New Zealand vineyards are planted mainly on flat alluvium and aggradation gravels with slopes of less than 3°. Rapid growth is pushing new plantings onto adjacent hillsides that are underlain by greywacke, schist, and (less commonly) limestone. The expansion of the industry onto these different substrates will affect grape and wine characteristics and may lead to new styles of New Zealand ultra-premium wines.